2018
DOI: 10.1111/ijpo.12476
|View full text |Cite
|
Sign up to set email alerts
|

The sequence of prenatal growth restraint and postnatal catch‐up growth: normal heart but thicker intima‐media and more pre‐peritoneal fat in late infancy

Abstract: Summary Background The sequence of prenatal growth restraint and postnatal catch‐up growth leads to a thicker intima‐media and more pre‐peritoneal fat by age 3–6 years. Objectives To study whether carotid intima‐media thickness (cIMT) and pre‐peritoneal fat differ already between catch‐up small‐for‐gestational‐age (SGA) infants and appropriate‐for‐gestational‐age (AGA) controls in late infancy (ages 1 and 2 years) and whether such differences – if any – are accompanied by differences in cardiac morphology and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
1
6
1
Order By: Relevance
“…While we found significantly increased diastolic mitral E- and A-wave peak inflow velocities, and an increased septal E / E ′ ratio in the SGA group, possibly indicating differences in ventricular filling, these differences were minor. Previous studies report both increased [ 6 ] and similar [ 12 ] E / E ′ ratios in SGA children during early childhood, while in the neonate stage, we found the E / E ′ ratio to be decreased in SGA and increased in LGA [ 13 ]. The increased left atrial volume observed in the LGA group suggests that diastolic function could potentially be affected by high birth weight.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…While we found significantly increased diastolic mitral E- and A-wave peak inflow velocities, and an increased septal E / E ′ ratio in the SGA group, possibly indicating differences in ventricular filling, these differences were minor. Previous studies report both increased [ 6 ] and similar [ 12 ] E / E ′ ratios in SGA children during early childhood, while in the neonate stage, we found the E / E ′ ratio to be decreased in SGA and increased in LGA [ 13 ]. The increased left atrial volume observed in the LGA group suggests that diastolic function could potentially be affected by high birth weight.…”
Section: Discussionsupporting
confidence: 61%
“…Birth weight associates with ventricular mass in early childhood [ 8 ] and adolescence [ 9 ], with higher birth weight associated with changes in diastolic function [ 10 ]. Recent studies have, however, demonstrated that SGA children show size-appropriate cardiovascular dimensions in early childhood [ 11 , 12 ], suggesting a limited impact of altered fetal growth. We have previously demonstrated cardiac morphology of SGA and LGA neonates to be appropriate for body size, with no evidence of altered geometry [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased carotid IMT has, in contrast to our findings, been linked with SGA during early childhood [ 9 ]. However, studies are inconclusive, as both increased carotid IMT [ 26 29 ] and normal carotid IMT [ 30 ], and increased [ 29 ] and normal [ 26 ] aortic IMT have been reported in SGA children, along with normal carotid IMT in LGA children [ 31 ]. We speculate that this could be due to limitations in conventional ultrasound axial resolution applied in earlier studies.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to AGA infants, those infants born small for-gestational age (SGA) were shown to have lower %BF by ADP at term birth [ 55 ]. According to Zegher et al, the greater levels of circulating preadipocyte factor 1 (Pref-1) found in SGA than in AGA newborns may partially explain the impaired intrauterine AT development [ 56 ], as Pref-1 has a role in suppressing adipocyte differentiation [ 57 ].…”
Section: Adipose Tissue Developmentmentioning
confidence: 99%